Cystatin C as a potential biomarker to evaluate migraine - AKDAĞ, Turan; UCA, Ali Ulvi (Arquivos de Neuro-Psiquiatria, 2020)
Background: Migraine is a multifactorial neurovascular syndrome and closely associated to inflammation. Cystatin C (Cys C) is a neuroendocrine polypeptide which also plays a role in inflammation. Objective: To investigate the levels of Cys C in migraine patients without aura. Methods: A total of 80 participants were included in the study; 40 patients and 40 healthy controls. Serum Cys C levels were investigated by using enzyme-linked immunosorbent assay (ELISA). Statistical analysis were performed using Statistical Package for the Social Sciences (SPSS) version 22.0 (SPSS Inc, IL, USA). Results: Serum Cys C levels were found as 73.88 ng/mL in the patient group and 24.92 ng/mL in the healthy control group, being significantly higher among patients (p=0.000). Serum Cys C levels were significacntly different across age subgroups among patients (p=0.049), but not among controls. However, visual analog scale (VAS) (p=0.707), disease duration time (p=0.725) and body mass index (p=0.136) were not significantly different between the two groups. Conclusion: Our findings demonstrate that high serum Cys C levels are independently associated to migraine without aura. To the best of our knowledge, this is the first study to determine the serum levels of Cys C in patients with migraine. Thus, serum Cys C may be a potential biomarker of migraine.
Keywords: Migraine Disorders; Cystatin C; Headache